The Influence of Firm Age on Profitability Performance of Indonesian Manufacturing Companies with The Age Level of Directors as Moderating Variable - Wibowo, Yohanes Kristantio; Honggowati, Setianingtyas (Jurnal Akuntansi dan Bisnis, 2022)
This research this study empirically investigates the effect of the age level of Board of Directors (BD) as moderating variable toward the influence of firm age on the corporate financial performance of manufacturing companies in Indonesia. Secondary data which were collected from the annual reports of 125 manufacturing companies listed on the Indonesia Stock Exchange (IDX), from year 2014 to 2017, are used as panel data for research sample of this study and regression analysis is applied on the proposed research models. The results of this study outline that the firm age of the listed Indonesian manufacturing companies has significant direct positive influence on the corporate financial performance as measured by accounting-based ratios of profitability, which include ROA, ROE, and NPM. However, the strength of influence of firm age on ROE depends on the effect of the age level of BD members as moderating variable. The higher the age level of BD members is proved to weaken the influence of firm age on ROE, while the lower the age level of BD members is proved to strengthen the influence of firm age on ROE. In addition, the age level of BD members also has significant negative influence on the corporate financial performance as measured by ROA and ROE. Thus, the age level of BD members can be regarded as Quasi Moderator of firm age on ROE. Ultimately, this study contributes to the limited body of corporate governance studies on the demographic factor of age of the corporate leaders, by outlining the indirect influence of the age level of the BD members toward the influence of firm age on the corporate financial performance in the context of economically developing country of Indonesia. Penelitian ini secara empiris menyelidiki pengaruh dari tingkat usia anggota Dewan Direksi (BD) sebagai variable moderasi pada pengaruh dari usia perusahaan terhadap kinerja keuangan perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia (BEI). Data sekunder yang dikumpulkan dari 125 laporan keuangan tahunan perusahaan manufaktur dengan periode tahun 2014 hingga 2017 digunakan sebagai data panel yang menjadi sampel penelitian dan analisis regresi diterapkan pada model penelitian dalam studi ini. Hasil analisis pada studi ini menunjukkan bahwa usia perusahaan terbukti memiliki pengaruh positif secara langsung yang signifikan terhadap kinerja keuangan perusahaan yang diukur dengan rasio profitabilitas berbasis akuntansi, yang meliputi ROA, ROE, dan NPM. Namun intensitas pengaruh dari tingkat usia perusahaan terhadap kinerja profitabilitas perusahaan yang diukur dengan ROE secara signifikan bergantung pada pengaruh dari tingkat usia anggota BD sebagai variabel moderasi. Semakin tinggi tingkat usia anggota BD dapat memperlemah pengaruh dari usia perusahaan terhadap ROE, namun Semakin rendah tingkat usia anggota BD dapat memperkuat pengaruh dari usia perusahaan terhadap ROE. Selain itu, tingkat usia anggota BD juga memiliki pengaruh negative secara langsung yang signifikan terhadap ROA dan ROE. Dengan demikian, tingkat usia anggota BD dapat dianggap sebagai Moderator Semu. Penemuan dari penelitian ini turut berkontribusi pada studi tata kelola perusahaan mengenai usia pemimpin perusahaan dengan menguraikan adanya pengaruh secara tidak langsung dari tingkat usia anggota BD pada pengaruh usia perusahaan terhadap kinerja keuangan perusahaan dalam konteks negara dengan kondisi ekonomi yang masih berkembang, Indonesia.